Synthesis of Single-Atom Catalysts Through Top-Down Atomization Approaches - Zhang, Aijing; Zhou, Mingzheng; Liu, Siyuan; Chai, Maorong; Jiang, Shengjuan (Frontiers in Catalysis, 2021)
Single-atom catalysts (SACs) have emerged as a hot research topic in recently years, and have been intensively investigated for energy storage and conversion applications. Significant advances in the synthesis of SACs have been achieved through enormous efforts in this area, however, their application is hindered by the low active site loading and poor long-term stability. In contrast with other methods, atomization, in which the SACs are synthesized from transformation of the nanoparticles to atomic sites, is a very attractive and innovative top-down approach to achieve high-density supported active sites with outstanding stability. However, limited attention has been paid to this area, despite the significant advances achieved in the past two years. In this short review, we discuss in detail the latest advances in atomization approaches for the synthesis of SACs and highlight the associated advantages and opportunities.